2021
DOI: 10.1016/j.nedt.2021.105064
|View full text |Cite
|
Sign up to set email alerts
|

Perception of online teacher self-efficacy: A multi-state study of nursing faculty pivoting courses during COVID 19

Abstract: Background COVID-19 forced many colleges and schools of nursing to abruptly pivot face-to-face learning to online formats. Online teaching is not new, but some faculty have not taught in a virtual environment and rapidly transitioning courses online was challenging. It is not known if teacher self-efficacy was impacted by these circumstances. Objectives We aimed to assess online teacher self-efficacy of nursing faculty who transitioned at least one-face-to face course t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…While comfort with the institutions learning management system made the transition of didactic content to an online platform relatively easy, the lack of pedagogic support to adapt active learning, lab, and clinical experiences into meaningful online instruction was an unexpected challenge with important consequences. As in other studies ( Culp-Roche et al, 2021 ), faculty struggled to develop lessons that supported students’ development of the psychomotor skills, interpersonal skills, and clinical judgment. Hawkins and Wiles (2020) reported that at the start of the pandemic, nearly 70% of nursing faculty had not taught online.…”
Section: Discussionmentioning
confidence: 88%
“…While comfort with the institutions learning management system made the transition of didactic content to an online platform relatively easy, the lack of pedagogic support to adapt active learning, lab, and clinical experiences into meaningful online instruction was an unexpected challenge with important consequences. As in other studies ( Culp-Roche et al, 2021 ), faculty struggled to develop lessons that supported students’ development of the psychomotor skills, interpersonal skills, and clinical judgment. Hawkins and Wiles (2020) reported that at the start of the pandemic, nearly 70% of nursing faculty had not taught online.…”
Section: Discussionmentioning
confidence: 88%
“…The significance in the student perception in terms of self-efficacy and expectations confirm the agreement with the literature on how essential self-efficacy is to online learning success. The quality of self-efficacy had significant the results revealed and impacts on satisfaction use of LMS based on prior experience (Alzahrani & Seth, 2021;Culp-Roche et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Self-efficacy belief is the result of individual emotion and the psychological thinking cognitive process ( Bandura, 1997 ). Meanwhile, teaching self-efficacy refers to the belief of teaching faculty in their ability to meet the challenges of teaching and to provide effective teaching for their students ( Culp-Roche et al, 2021 ). In this study, online teaching self-efficacy (OT-SE) could be regarded as the evaluation and judgment of whether teachers are competent to perform online teaching tasks when they carry out online education.…”
Section: Literature Reviewmentioning
confidence: 99%